Endoscopic transchoroidal approach to pineal region tumour with splitting of the massa intermedia. (31st January 2018) - Burford, Charlotte; Kalyal, Nida; Minichini, Viviana; Lavrador, Jose; Kailaya-vasan, Ahilan; Zebian, Bassel
Abstract: OBJECTIVE: Combined endoscopic third ventriculostomy (ETV) and tumour biopsy is a common approach to the management of patients presenting with hydrocephalus secondary to a pineal region lesion. We report our experience in performing an ETV and limited debulking of a pineal tumour using a rigid scope through a single burr hole. This was made possible by splitting the choroid fissure (CF) and massa intermedia (MI). We also report our review of the literature of current endoscopic approaches to the biopsy of pineal region lesions combined with ETV. SUBJECT: A 13-year-old boy presented with a two-day history of rapidly progressive headache with blurred vision, diplopia and vomiting. Brain MRI revealed a pineal region lesion associated with obstructive hydrocephalus. RESULTS: An endoscopic transchoroidal approach with splitting of the MI combined with an ETV was performed. This allowed successful management of the obstructive hydrocephalus and a limited debulking of the pineal tumour. The histopathologic examination revealed an immature teratoma. Post-operatively the patient made an uneventful recovery and started chemotherapy. CONCLUSION: The endoscopic transchoroidal approach with splitting of the massa intermedia, when possible, allows management of the hydrocephalus and biopsy/debulking of pineal tumours through a single burr hole even when a solid scope is used. With experience and improved instrumentation, complete endoscopic resection of pineal tumours may become common-place in the future.